Race & Prejudice: Constructing Race Identity in “The Help” Movie (2011) - Arfian Dwi Saputra; Gracia Petra Theresa; Happy Kurnia; Tedi Setyawan; Wahyu Rismayuda Dwitama; M. Afifulloh (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
This study aims to describe and analyse the representation of racism in the film "The Help." The research method used are descriptive qualitative and content analysis to identify how the concepts of racism, stereotypes, and power are displayed in the film's narrative. The theory used in this study is the "Theory of Prejudice" proposed by Gordon Allport, which helps in understanding how negative perceptions of certain groups can develop into discriminatory attitudes and actions. The results of this study provide deep insight into how racism is presented in entertainment media and its impact on social consciousness.